Question and Answers Forum

All Questions      Topic List

Arithmetic Questions

Previous in All Question      Next in All Question      

Previous in Arithmetic      Next in Arithmetic      

Question Number 193438 by Mingma last updated on 14/Jun/23

Answered by qaz last updated on 14/Jun/23

log_3 (9x−3)=1+log_3 (3x−1)     ,log_3 (x−(1/3))=log_3 (3x−1)−1  log_3 (3x−1)=y  (√(1+y))≤y−1    ⇒y≥3     ⇒x∈[((28)/3),+∞)

$${log}_{\mathrm{3}} \left(\mathrm{9}{x}−\mathrm{3}\right)=\mathrm{1}+{log}_{\mathrm{3}} \left(\mathrm{3}{x}−\mathrm{1}\right)\:\:\:\:\:,{log}_{\mathrm{3}} \left({x}−\frac{\mathrm{1}}{\mathrm{3}}\right)={log}_{\mathrm{3}} \left(\mathrm{3}{x}−\mathrm{1}\right)−\mathrm{1} \\ $$$${log}_{\mathrm{3}} \left(\mathrm{3}{x}−\mathrm{1}\right)={y} \\ $$$$\sqrt{\mathrm{1}+{y}}\leqslant{y}−\mathrm{1}\:\:\:\:\Rightarrow{y}\geqslant\mathrm{3}\:\:\:\:\:\Rightarrow{x}\in\left[\frac{\mathrm{28}}{\mathrm{3}},+\infty\right) \\ $$

Commented by Mingma last updated on 14/Jun/23

Perfect ��

Terms of Service

Privacy Policy

Contact: info@tinkutara.com